Le Canada et le régime international de l’aide - Thérien, Jean-Philippe (Études internationales, 1989)
This article examines the conditions of production for Canadian policy in development and. Traditionally, analysis of Canadian aid has followed either a pluralistic, statist or neo-marxist theoretical approach. Noting the inadequacy of these forms of explanation, the author proposes an interpretation of Canadian aid based on the concept of « international community. » This concept can be defined as being the totality of decision-making principles, norms, rules and procedures that structure the expectations and behaviours of those involved in areas dealing with international relations.By resorting to this notion of international community, this study intends to demonstrate that the conditions of production for Canadian aid encompass two kinds of determinism. First, on the systemic level Canadian policy can be perceived as the result of external pressures to put in place an international aid community that contributes to regulating North-South relations. Second, on the national level Canadian aid can be seen as the product of internal power relationships which translate into pressures on the State to modify its participation in the international aid community so as to ensure the promotion of specific political interests.